Increasing Literacy Through Interactive Media In Early Childhood - Iin Purnamasari (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
The purpose of the study is to develop interactive learning media to improve early childhood literacy. The type of research is Research and Development/RD using the ADDIE model development procedure. The subjects of the study included 21 groups of Class A in Al Azhar kindergarten. Data collection techniques use interviews, FGD (Focus Group Discussion), observation, and validation of material and media experts. Data were analyzed with descriptive statistics and effectiveness tests. Research results in the development of interactive learning multimedia products that are valid, effective, and feasible to be used to improve early childhood literacy. The effectiveness of the media is shown from the results of the t-test, which is known that that learning with interactive media can improve early childhood literacy.